Skin grafting treatment of adolescent lower limb avulsion injury - Yang, Liu; Guo, Jiachao; He, Jinpeng; Shao, Jingfan (Frontiers in Surgery, 2022)
Background Under the influence of various factors, the number of lower extremity avulsion injuries in adolescents is increasing year by year. The main modality of treatment is skin grafting. There are many types of skin grafting. Although many studies on skin grafting after avulsion injuries have been published in the past few decades, there are differences in the treatment options for adolescents with post avulsion injuries. Main body Thorough debridement and appropriate skin grafts are essential for the surgical management of avulsion injuries for optimal prognosis. In the acquisition of grafts, progress has been made in equipment for how to obtain different depths of skin. The severity of the avulsion injury varies among patients on admission, and therefore the manner and type of skin grafting will vary. Especially in adolescents, graft survival and functional recovery are of great concern to both patients and physicians. Therefore, many efforts have been made to improve survival rate and activity. Conclusion This review summarizes the principles of treatment of avulsion injuries, the historical development of skin grafts, and the selection of skin grafts, hoping to be helpful for future research.